Real wages and the business cycles in Germany - Martyna Marczak; Thomas Beissinger (Institute for the Study of Labor (IZA), 2010)
This paper establishes stylized facts about the cyclicality of real consumer wages and real producer wages in Germany. As detrending methods we apply the deterministic trend model, the Beveridge-Nelson decomposition, the Hodrick-Prescott filter, the Baxter-King filter and the structural time series model. The detrended data are analyzed both in the time domain and in the frequency domain. The great advantage of an analysis in the frequency domain is that it allows to assess the relative importance of particular frequencies for the behavior of real wages. In the time domain we find that both real wages display a procyclical pattern and lag behind the business cycle. In the frequency domain the consumer real wage lags behind the business cycle and shows an anticyclical behavior for shorter time periods, whereas for longer time spans a procyclical behavior can be observed. However, for the producer real wage the results in the frequency domain remain inconclusive.
Keywords: E32; C22; C32; J30; 330; real wages; business cycle; frequency domain; time domain; Germany; trend-cycle decomposition; structural time series model; phase angle; Reallohn; Konjunktur; Zeitreihenanalyse; Konsumgüterindustrie; Verarbeitendes Gewerbe; Schätzung; Deutschland